2010
DOI: 10.1021/bi901798g
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Study of the Role of M42 in the Solution Dynamics of Escherichia coli Dihydrofolate Reductase

Abstract: It is widely recognized that key positions throughout a protein’s structure contribute unequally to function. In light of recent studies that suggest protein dynamics are required for function, a number of these residues may serve to promote motions required for ligand binding and catalysis. In the present NMR study, the conformational dynamics of the dihydrofolate reductase (DHFR) mutant M42W, in the presence of methotrexate and NADPH, are characterized and compared to the wild-type enzyme. M42 is distal to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 62 publications
(185 reference statements)
1
42
0
Order By: Relevance
“…RDCs provide long-range orientation information on the NH bond vector and are often used to assess structural perturbations upon mutation (50) and ligand binding (51). We chose pH 6.0 because the solution structure of the FAT domain had been solved at this pH (19).…”
Section: Resultsmentioning
confidence: 99%
“…RDCs provide long-range orientation information on the NH bond vector and are often used to assess structural perturbations upon mutation (50) and ligand binding (51). We chose pH 6.0 because the solution structure of the FAT domain had been solved at this pH (19).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, recent studies on dihydrofolate reductase (56), triosephosphate isomerase (57), ribonuclease A (58), HIV-1 reverse transcriptase (59), and imidazole glycerol phosphate synthase (60) show that slow microsecond to millisecond motions are severely dampened when these enzymes are inhibited (56,59,60) or when catalytically hindering mutations are introduced (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…(20) We do not observe this elongated ADL in the double mutation. If anything, there seems to be a slight compression both in the Michaelis complex and in the transition state since both mutations introduce steric congestions propagated to the active site,(21-22) especially in the M42W mutation site(28) (see below).…”
Section: Reduced Protein Flexibility At the Transition State Is Rmentioning
confidence: 99%
“…(18-19, 21-22, 68-70) Mauldin et al showed that the M20 loop adopts the closed conformation in the ternary complex with NADPH and methotrexate both in the M42W and G121V mutants. (21-22) While the G121V mutantion results in a large response on the M42 dynamic fluctuations from NMR relaxation experiments,(21) the M42W mutation showed that the M42 site serves has a hob connecting the dynamic fluctuations throughout the protein. (22) The M20 conformational fluctuations in the wt-DHFR and single and double mutants at M42 and G121 as well as their coupled motions in the Michaelis complex have been examined by Brooks and coworkers.…”
Section: Reduced Protein Flexibility At the Transition State In mentioning
confidence: 99%